Transformasi Narapidana melalui Kewirausahaan Agribisnis: Membangun Keberlanjutan Usaha dan Mengurangi Residivisme - Fernando, Agus (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2025)
This study is based on capacity-building theory, a key component of change theory, which emphasizes the importance of developing individual and organizational capacity to achieve sustainable change. In the context of correctional institutions (LAPAS), this theory helps explain how empowerment programs can improve inmates' ability to prepare for life after their sentence, with the aim of reducing recidivism through sustainable entrepreneurial skills. This study focuses on evaluating the impact of an agricultural entrepreneurship promotion program in Class IIA Cikarang Correctional Facility (LAPAS) on business sustainability and recidivism rates. The study used partial least squares structural equation modeling (PLS-SEM) to develop two analytical models. Model 1 covers all respondents, while Model 2 covers inmates with no entrepreneurial experience or training. The main variables in this study include technical skills, entrepreneurial skills, social support, education and knowledge, motivation, business sustainability, and recidivism rates. The results of Model 1 show that technical skills, entrepreneurial skills, social support, and education have a positive impact on business sustainability, which contributes to reducing recidivism rates. Motivations and attitudes affect enterprise sustainability but have no direct effect on recidivism rates. Model 2 shows that technical skills and business sustainability significantly reduce recidivism rates, while entrepreneurial skills and social support act as mediators. The study concludes that agricultural business programs are very important for the economic sustainability and reduction of recidivism rates of prisoners after release, and recommends more intensive agricultural training and improved social support.